2013
DOI: 10.1177/0748233713480209
|View full text |Cite
|
Sign up to set email alerts
|

Role of apoptosis in mediating diclofenac-induced teratogenesis

Abstract: Diclofenac (DCF) is among the most commonly used nonsteroidal anti-inflammatory drugs worldwide for the treatment of various conditions in postpubertal women. However, very limited information is available regarding its safety during pregnancy and teratogenecity. The present study was designed to elucidate the effects of DCF on the developing rat embryos during the major organogenesis period and investigate the critical role of apoptosis in bringing about these congenital anomalies. Embryos were exposed in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Drug-induced oxidative stress can primarily recruit rescue pathways, but, if sustained, the stress can cause mitochondrial injury 65,66 . Thus, the cells are usually not able anymore to repair the damage, and apoptotic or necrotic events mainly occur 6769 .…”
Section: Discussionmentioning
confidence: 99%
“…Drug-induced oxidative stress can primarily recruit rescue pathways, but, if sustained, the stress can cause mitochondrial injury 65,66 . Thus, the cells are usually not able anymore to repair the damage, and apoptotic or necrotic events mainly occur 6769 .…”
Section: Discussionmentioning
confidence: 99%
“…Diverse studies using other NSAIDs also found significant growth inhibition (Chae et al, 2015;Fort et al, 1992;Veldhoen et al, 2014). While Singh et al (2015) found that exposure to DCF in a rat embryo culture reduced overall growth and developmental parameters such as embryo weight, head-to-tail length and number of somites in vitro in a concentration-dependent pattern, and that the mechanism of teratogenicity of DCF may be oxidative stress induction leading to an abrupt increase in apoptosis, while the uncontrolled pattern of this cell death process results in diverse malformations whose severity depends on pharmaceutical concentration. Previous studies have reported DCF induction of oxidative stress and genotoxicity in aquatic organisms Fig.…”
Section: Mexican Effluent Type (Reference)mentioning
confidence: 97%